Trends in dietary supplement use among athletes selected for doping controls - Lauritzen, Fredrik; Gjelstad, Astrid (Frontiers in Nutrition, 2023)
Background Dietary supplements (DS) may be beneficial for athletes in certain situations, whereas incorrect or excessive use may impair performance, pose a risk to the athlete´s health and cause positive doping tests by containing prohibited substances. To provide athletes with relevant and tailored information on safe supplement use, a better knowledge about DS trends over time and between sport disciplines are needed. Methods This study examines the use of DS among athletes who have participated in doping controls by extracting information derived from 10 418 doping control forms (DCF) collected by Anti-Doping Norway from 2015 to 2019. Results Overall, 51% of the DCFs contained information about at least one DS. National level athletes (NLA) more often reported using DS than recreational athletes (RA) (53% vs. 47%, p<0.001). Athletes in strength and power (71%), VO2max endurance (56%) and muscular endurance sports (55%) had the highest proportion of DCFs with information about DS. Medical supplements were the most used supplement category for both genders and across all sports. DS with a high risk of containing doping substances were most common among male, RA in strength and power sports. There were small and non-significant year-to-year variations in the prevalence of athletes using DS, while the number of products used concomitantly peaked in 2017 before declining in 2019 (2.30 vs. 2.08, p<0.01). The use of medical supplements and ergogenic substances increased slightly for both NLA and RA from 2015 to 2019, while the use of all other supplement categories declined. Conclusion Half of the 10 418 DCFs contained information about DS, with variations within the athlete population. DS with high risk of containing prohibited substances were mostly seen in sport disciplines requiring a high degree of specialization in strength/power, including powerlifting and weightlifting, as well as in some team sports, such as cheerleading and American football.